Pengaruh Pemasaran Humas terhadap Kesadaran Merek pada Produk Cimory di Cimory Dairy Shop Cawang - Supendi, Moh.; Suyadi, Suyadi; Herviani, Dian (Utilitas, 2017)
This study aimed to determine the effect of Public Relation Marketing to Brand Awareness of Cimory products at Cimory Dairy Shop Cawang. This research used associative quantitative research method. The research population of this study were 380 costumers and the sample were 79 respondents, chosen by incidental sampling technique. The data examined by normality test and homogenity test. Then, conducted the analysis of variance test (ANAVA) as prerequisites to next analysis. The results of linear regression calculations showed that ,36 + 0,53(X) and the calculation of ANAVA obtained Fcount < Ftable (0,2975 < 1, 74). The hypothesis testing was done by the Pearson’s product moment correlation to obtain . That showed the strong influence of Public Relation Marketing to Brand Awareness at Cawang based Cimory Dairy Shop. The value is compared to the criteria interpretations of correlation coefficient table interpretation as 0.600 – 0.799. Therefore, the study concluded that there was the influence of Public Relation Marketing to Brand Awareness of Cimory products at Cimory Dairy Shop Cawang. Keywords: Public Relation Marketing, Brand Awareness, Quantitative Associative Research